EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DAMPAKNYA TERHADAP KINERJA KARYAWAN PADA PT. INDOMETRIX BANDUNG - Rina Kurniawati; Ardelia Astriany Rizky (POLITEKNIK PIKSI GANESHA, 2020)
Accounting Information System (SIA) is an application used to help employees of PT. Indometrix Bandung in processing company financial data with the aim of improving employee performance. The purpose of this study was to determine the effectiveness of the Accounting Information System (SIA) on the performance of employees at PT. Indometrix Bandung. And this research is expected to provide input to further improve employee performance. The research method used is qualitative and quantitative methods. Data collection techniques using observation, interviews and questionnaires. The unit of analysis in this study was employees as respondents. For data analysis using Pearson Product Moment correlation technique, coefficient of determination and t test to test the hypothesis. Meanwhile, data processing uses the help of SPSS 15 For Windows and MSI (method of successful interval). The results showed that the respondents gave a good response to the Effectiveness of Accounting Information Systems, but the responses of respondents to the indicator system use are still in the category enough. Furthermore, the response of respondents to the Employee Performance is good, but for the indicator Cooperation and Initiative are still in the category enough. Correlation test results obtained showed a close relationship, while the magnitude of Accounting Information Systems Effectiveness influence on the performance of employees at 58.5%, and the result is known that the more effective use of Accounting Information Systems will create higher employee performance, and vice versa, the less effective use of Accounting Information Systems will make the lower the employee's performance.